Strategies Sales and Marketing at Echoboom Management - Salvi, Siddhesh (ATLAS SkillTech University, 2024)
Core mission is to deliver business, marketing, manpower planning, training and development-related advisory services. Our aim is to create value propositions for our clients and commit to effective implementation. Our consulting services go beyond mere advice: we share our clients’ goals. Our main goal is to exceed our clients’ expectations and become their trusted partners. We work "with" them, combining performance and excellence as the key objectives in all our professional partnerships. Our differentiating factor lies in our in-depth knowledge of the businesses in which our clients operate.
Project Report on Strategies Sales and Marketing at Echoboom Management (2022-2024) Under the Guidance of Prof. Ameya Ambulkar
Keywords: Clients; TECHNOLOGY::Industrial engineering and economy::Physical planning